Radon Improves Clinical Response in an Animal Model of Rheumatoid Arthritis Accompanied by Increased Numbers of Peripheral Blood B Cells and Interleukin-5 Concentration - Deloch, Lisa; Hehlgans, Stephanie; Rückert, Michael; Maier, Andreas; Hinrichs, Annika; Flohr, Ann-Sophie; Eckert, Denise; Weissmann, Thomas; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Rödel, Franz; et al. (Cells, 2022)
Radon treatment is used as an established therapy option in chronic painful inflammatory diseases. While analgesic effects are well described, little is known about the underlying molecular effects. Among the suspected mechanisms are modulations of the anti-oxidative and the immune system. Therefore, we aimed for the first time to examine the beneficial effects of radon exposure on clinical outcome as well as the underlying mechanisms by utilizing a holistic approach in a controlled environment of a radon chamber with an animal model: K/BxN serum-induced arthritic mice as well as isolated cells were exposed to sham or radon irradiation. The effects on the anti-oxidative and the immune system were analyzed by flow-cytometry, qPCR or ELISA. We found a significantly improved clinical disease progression score in the mice, alongside significant increase of peripheral blood B cells and IL-5. No significant alterations were visible in the anti-oxidative system or regarding cell death. We conclude that neither cell death nor anti-oxidative systems are responsible for the beneficial effects of radon exposure in our preclinical model. Rather, radon slightly affects the immune system. However, more research is still needed in order to fully understand radon-mediated effects and to carry out reasonable risk-benefit considerations.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Anti-oxidative system; B cells; Immune system; Inflammation; Macrophages; Monocytes; Radon therapy; Rheumatoid arthritis; Serum transfer arthritis; T cells